An Analisis of Students’ Perception of Online Learning in Micro-Teaching Class at English Department UNP - Veni Rozela Arfi; Nora Fudhla (Journal of English Language Teaching, 2021)
The purpose of this study was to analyze students' perception of online learning in micro-teaching class at English department of UNP. The sort of study that will use a survey approach to perform quantitative descriptive research. The population in this study were all students of the 2018 English Department UNP entrance year. This study uses a proportional random sampling technique, proportional random sampling is a sampling technique where all members have the same opportunity to be sampled according to their proportions, large or small population. From the slovin formula, it can be seen that 105 students will be sampled in this research by distributing questionnaires using a Likert scale. In addition, the data obtained were described, then a description of the research results was carried out using SPSS and the categorization based on the Mean and Standard Deviation.